1972
DOI: 10.1111/j.1365-246x.1972.tb02360.x
|View full text |Cite
|
Sign up to set email alerts
|

Source Time Functions and Spectra for Underground Nuclear Explosions

Abstract: The model of Haskell for explosion source time functions and spectra fails to satisfy data in the short-period band recorded teleseismically from the three Amchitka Island underground nuclear tests: LONG-SHOT, MILROW, and CANNIKIN. A more recent model due to Mueller and Murphy satisfies the data quite well. The difference in the two models is basically in the fall-off at high frequencies. A simple revision of Haskell's model produces waveforms and spectra nearly identical to ones from Mueller and Murphy's mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…There appears to be a real dif- tempt is made to quantitatively relate these patterns to observed LR amplitudes since we cannot corr ect the predicted amplitudes for source mechanism, but we can qualitatively compare the pattern of rays to M 5 residuals calculated from the magnitude data in Table IV . (The rays which pass close to the North Pole were stopped close to that point due to ray-tracing numerical problems near von Seggern , B., and R. Blandford (1972). Source time functions and spectra for underground nuclear explosions , Geophys.…”
Section: Imentioning
confidence: 99%
“…There appears to be a real dif- tempt is made to quantitatively relate these patterns to observed LR amplitudes since we cannot corr ect the predicted amplitudes for source mechanism, but we can qualitatively compare the pattern of rays to M 5 residuals calculated from the magnitude data in Table IV . (The rays which pass close to the North Pole were stopped close to that point due to ray-tracing numerical problems near von Seggern , B., and R. Blandford (1972). Source time functions and spectra for underground nuclear explosions , Geophys.…”
Section: Imentioning
confidence: 99%
“…Another possible explanation is that, because of the low magnitudes of events studied here, a clear von Seggern, D., and R. Blandford, 1972. Source time functions and spectra for underground nuclear explosions, Geophys.…”
Section: Ms-m Bmentioning
confidence: 91%
“…These include. for example, work by , Haskell (1967), Mueller & Murphy (1971), von Seggern & Blandford (1972), and HeIberger & Hadley (1981. Evernden et al, (1986) find that the Sharpe model approximates observed explosive source spectra from NTS reasonably well.…”
Section: Ville/salut Spectral Ratiosmentioning
confidence: 99%